2008
DOI: 10.4049/jimmunol.180.3.1694
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles for the E2A Activation Domains in B Lymphocytes and Macrophages

Abstract: The E2A gene encodes two E protein/class I basic helix-loop-helix transcription factors, E12 and E47, that are essential for B lymphopoiesis. In addition to the DNA-binding and protein dimerization domain, the E proteins share two highly conserved transcription activation domains. In this study, we show that both activation domains are required for optimal E2A-dependent transcription. Surprisingly, however, neither activation domain is required for E2A to rescue B lymphopoiesis from E2A−/− hemopoietic progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 46 publications
5
34
1
3
Order By: Relevance
“…This result is consistent with a recent study (Bhalla et al 2008) showing that an E2A mutant lacking both AD1 and AD2 retains the ability to promote B lymphopoeisis with associated activation of B-lineage genes when ectopically expressed in primary E2A À/À fetal liver multipotent progenitors. This likely reflects the activity of the residual AD3 domain in the ectopic E2A, since expression of the bHLH (DNA-binding) domain of E2A failed to support B-cell development and gene activation.…”
Section: Multiple E-protein Activation Domains: Functional Cooperativsupporting
confidence: 82%
“…This result is consistent with a recent study (Bhalla et al 2008) showing that an E2A mutant lacking both AD1 and AD2 retains the ability to promote B lymphopoeisis with associated activation of B-lineage genes when ectopically expressed in primary E2A À/À fetal liver multipotent progenitors. This likely reflects the activity of the residual AD3 domain in the ectopic E2A, since expression of the bHLH (DNA-binding) domain of E2A failed to support B-cell development and gene activation.…”
Section: Multiple E-protein Activation Domains: Functional Cooperativsupporting
confidence: 82%
“…Two activation domains, AD1 and AD2, are located at the N-terminal half of the proteins and have both redundant and distinct functions. AD1 can function as either an activation domain or a repression domain depending on cellular context (Markus et al 2002;Bhalla et al 2008). A conserved LDFS motif in AD1 recruits the SAGA complex (Massari et al 1999) and is also the region that interacts with the repressor protein ETO (Zhang et al 2004), which might account for the alternative activation and repression functions of AD1.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-function studies have indicated that an interaction between the PCET motif within activation domain 1 of E-proteins and the KIX domain of CBP/p300 is involved in B-lymphopoiesis, 3,12 is targeted in a mechanism of E-protein silencing, 9 and is essential for E2A-PBX1 oncogenesis. 16 KIX also binds activation domains of several other mammalian transcription factors 10,13,37,38 and viral proteins [39][40][41] involved in the regulation of lymphopoiesis through their LXXLL sequence or more generic -x-x--sequence described by Lee et al, 10 which is typically preceding by an acidic residue (; Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…Each member contains a C-terminal bHLH domain responsible for protein dimerization and recognition of the E-box DNA sequence CANNTG as well as 2 activation domains, AD1 and AD2, which function either independently or cooperatively depending on cell type to regulate target gene transcription through the recruitment of transcriptional coactivators and corepressors. 1,[3][4][5] A highly conserved 17-residue region within AD1 at the N-terminus of E-proteins is the target of the eTAFH domain from the transcriptional corepressor ETO and the oncogenic fusion protein AML-ETO. [6][7][8][9] This interaction leads to E-protein silencing by preventing the binding of the transcriptional coactivators p300/CBP to the same site on AD1, which has been termed the "p300/CBP and ETO target in E-proteins" (PCET) motif.…”
Section: Introductionmentioning
confidence: 99%